Empirical essays on trade openness, total factor productivity growth and efficiency - Henry, Michael (2004)
This thesis is concerned with understanding the factors responsible for the vast differences in per capita income levels and growth rates evident across countries. As part of this inquiry, it examines the role played by international trade both singly and in combination with geography, institutions and foreign R&D.